Monetary Income and Expenditures of Single Farmers of Sverdlovsk Region (according to Budget Surveys of 1960) - V. N. Mamyachenkov (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The article is devoted to the subject insufficiently developed in the national historiography, especially in regard to its regional dimension. The study is conducted on materials of three archives: State archive of Sverdlovsk region, Russian state archive of Economics and the Centre of documentation of public organizations of Sverdlovsk region with the assistance of the scientific and publicistic literature. The relevance of the topic is determined by its importance for the social sciences, especially for history. Scientific novelty of the work is seen in the fact that the new materials discovered by the author in these archives are introduced into scientific usage. The article aims to study the monetary income and expenditures of single farmers of Sverdlovsk region in 1960. It is noted that the most credible source for research are the data of budget surveys. It is argued that these materials were long closed to researchers and have become available for development relatively recently. It is emphasized that these materials must be subjected to comprehensive analysis, also using the mathematical apparatus. It is stated that there was a pretty serious differentiation of monetary income of the surveyed farmers. It is stated that only farmers of certain households that for various reasons were in a privileged position had relatively high income. It is proved that the most part of farmers’ expenses were the purchase of livestock and poultry, agricultural products and industrial goods (including food). It is declared that from the economic point of view private farming had two important functions: firstly, it formed, as a rule, food ration of the farmers, and secondly, was the main source of money in the farmhouse. It is concluded that with the income from household plots total revenue of farmers to some extent were comparable to that of urban residents.